TIPOLOGI BARU PASAR TRADISIONAL SERPONG - Nadhifa Aurelia Prawira; Sidhi Wiguna Teh (Jurusan Arsitektur dan Perencanaan, 2022)
Serpong E-Peken Project: A New Form of Serpong Traditional Market is based on the problems that arise and affect most of the traditional markets in Indonesia. Traditional markets are often considered slum and unfit, especially for the upper middle class, this makes the market undeveloped due to its inability to compete with the emergence of modern markets. Though this problem should not happen because every market has its own characteristics. The construction of this project is based on a conceptual method, which in its development takes into account many factors, both external and internal. In addition, this project also combines several other functions outside of its main function, such as a food court area, a sitting area as well as a communal area, and a recreation area to keep activities in the market alive. By using this method, it is hoped that this project will be able to carry out its main function as a traditional market and also be able to increase its competitiveness. This new form of traditional market is also expected to increase public interest in traditional markets and can be used as an example in the development of other traditional markets in the future. Keywords: Market Revitalization; Rethinking Typology; Traditional Market. AbstrakProyek E-Peken Serpong: Wujud Baru Pasar Tradisional Serpong diangkat dari permasalahan yang muncul dan menimpa sebagian besar pasar tradisional yang ada di Indonesia. Pasar tradisional kerap dinilai kumuh dan tidak layak khususnya bagi masyarakat kelas menengah atas, hal ini membuat pasar tidak berkembang karena ketidakmampuannya untuk bersaing dengan bermunculannya pasar - pasar modern. Hal ini tidak seharusnya terjadi sebab setiap pasar memiliki karakteristik yang berbeda. Pembangunan proyek ini berbasis metode konseptual, dimana dalam pembangunannya memperhatikan banyak faktor baik eksternal maupun internal. Selain itu, proyek ini juga menggabungkan beberapa fungsi lain di luar fungsi utamanya, seperti area food court, area duduk sekaligus area komunal, dan area rekreasi agar aktivitas di dalam pasar tetap hidup. Dengan menggunakan metode tersebut diharapkan proyek ini akan mampu menjalankan fungsi utamanya sebagai pasar tradisional dan juga mampu meningkatkan daya saingnya. Wujud baru pasar tradisional ini juga diharapkan akan meningkatkan minat masyarakat akan pasar tradisional dan bisa dijadikan contoh dalam pengembangan pasar tradisional lainnya di kemudian hari.